1977
DOI: 10.1088/0031-9120/12/5/008
|View full text |Cite
|
Sign up to set email alerts
|

A misinterpretation of Bernoulli's theorem

Abstract: somewhat intangible outcome; the actual materials might then be regarded as of only incidental importance. Inevitably the tests and self-teaching materials must have a limited lifetime of applicability-as yet unknown-but experience in producing and using them is likely to make the provision of the next generation of such materials a simpler task. After all, the ultimate aim must be to make the school-university interfacing problems disappear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In particular, its application on different current lines or unconfined flows can lead to incorrect predictions. This aspect has been discussed in numerous studies, for example [18][19][20][21][22][23][24].…”
Section: B Bernoulli's Equation In the Context Of Ideal Fluid Hydrody...mentioning
confidence: 99%
“…In particular, its application on different current lines or unconfined flows can lead to incorrect predictions. This aspect has been discussed in numerous studies, for example [18][19][20][21][22][23][24].…”
Section: B Bernoulli's Equation In the Context Of Ideal Fluid Hydrody...mentioning
confidence: 99%
“…Quantitative agreement then results, as demonstrated here, and a Galilean-invariant expression for the pressure drop along a horizontal tapered pipe can be obtained. where equation (1) was used to eliminate υ 2 in favour of υ 1 . The right-hand side of equation (A.7) is integrated from r 2 to r 1 to get the work W taper done on the fluid by the taper.…”
Section: Discussionmentioning
confidence: 99%
“…However, pressure is a Galilean invariant and must therefore be the same in either frame of reference (since neither force nor area varies from one inertial frame to another). So we now have the paradoxical situation that the speed of the water is larger in the wide pipe where the pressure is higher [1]. How can that be?…”
Section: Introductionmentioning
confidence: 99%
“…In fluid mechanics, literature on teaching, formative assessment, remedial instruction, and tools are expanding much more than excepted. It has been reported that concepts from pressure and fluid statics [57,[60][61][62][63][64][65], to Archimedes' principle [66], to Bernoulli's law often lead to misunderstandings [67][68][69][70][71][72]. To combat such misconceptions, various studies have developed approaches such as CFD instrumentation, e-learning, experimental hands-on implementation, interview analyses, student engagement, and interactive learning techniques, among others [73][74][75][76][77][78][79][80].…”
Section: Work In Progress In Learning and Teaching Fluid Mechanicsmentioning
confidence: 99%